Interventions for treating posterior cruciate ligament injuries of the knee in adults: A systematic review and meta-analysis protocol - Jorge Sayum Filho; Marcel Jun Sugawara Tamaoki; Rogerio Teixeira de Carvalho; Álvaro Nagib Atallah; Fabio Teruo Matsunaga; Flávio Faloppa; João Carlos Belloti (PLoS ONE, 2025)
Introduction There are many different surgical and conservative interventions for treating posterior cruciate ligament (PCL) injuries of the knee in adults. However, in the literature, there is no consensus regarding the best intervention for treating these patients. The objective of this systematic review and meta-analysis is to analyse the effectiveness of interventions (surgical and conservative) for treating PCL injuries of the knee in adults. Methods and analysis Starting in November 2025, the authors will accomplish a detailed search using the MEDLINE/PubMed, EMBASE, Cochrane Central Register of Controlled Trials and LILACS databases. Relevant gray literature (academic papers, reference lists theses, technical reports and conference abstracts) will also be included. Two authors will independently screen and extract the information found from randomized controlled trials in the literature. The bias and quality of the included studies will be evaluated using the Risk of Bias 2 tool provided by the Cochrane Collaboration. Statistical analyses will be performed using Review Manager V.5.4/Review Manager Web software. Discussion This systematic review is aimed at providing practical information for Orthopaedic surgeons on the effectiveness of the interventions (surgical and conservative) for treating PCL injuries of the knee in adults. PROSPERO registration number CRD42023430493.